2016
DOI: 10.1063/1.4942995
|View full text |Cite|
|
Sign up to set email alerts
|

Porosity as a function of stoichiometry and implantation temperature in Ge/Si1−xGex alloys

Abstract: The development of porosity in single-crystal germanium and silicon-germanium alloys (c-Si1−x Gex) of (100) orientation was studied under bombardment with 140 keV Ge− ions over a wide range of temperatures (−180 to 400 °C) and ion fluences up to 1 × 1018 ions/cm2. The surface swelling and morphology were investigated using multi-characterization techniques including optical profilometry, transmission electron microscopy, and scanning electron microscopy. The initiation of porosity and the evolution of the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In this case, the top 2/3rd of the a-Ge layer contains large columnar pores that intersect the surface, consistent with typical porosity microstructure in irradiated Ge. 14,15 In contrast, capping the surface with a SiO 2 layer of 20 nm thickness totally eliminated pore formation at LN 2 T at the same Sn fluence as shown in Fig. 1(c).…”
Section: Resultsmentioning
confidence: 89%
“…In this case, the top 2/3rd of the a-Ge layer contains large columnar pores that intersect the surface, consistent with typical porosity microstructure in irradiated Ge. 14,15 In contrast, capping the surface with a SiO 2 layer of 20 nm thickness totally eliminated pore formation at LN 2 T at the same Sn fluence as shown in Fig. 1(c).…”
Section: Resultsmentioning
confidence: 89%
“…25. Indeed, it is demonstrated 20 that vacancies preferentially form clusters and voids at the a-Ge surface during ion irradiation leading to pores that intersect the surface and develop with increasing fluence into a porous structure like that in Fig. 4(d).…”
mentioning
confidence: 99%
“…It was shown, however, that achieving Sn concentrations in Ge higher than about 6 at:% through ion implantation is severely hindered by a high sputtering effect in Ge and the onset of ionimplantation induced porosity once the Ge is rendered amorphous (a-Ge). 18 It has previously been found that irradiation-induced porosity is favoured in the range of implant temperatures between $ À 80 C and $200 C. [19][20][21] The onset of porosity can be suppressed by undertaking implants outside of this unfavourable temperature window. At elevated temperatures above 200 C, the Ge substrate remains crystalline due to the recombination of mobile vacancies and interstitials.…”
mentioning
confidence: 99%
See 2 more Smart Citations